THE DEVELOPMENT OF STUDENTS WORKSHEET BASED ON MULTIPLE INTELLIGENCES FOR THE SOURCE OF MATERIALS FOR COLLOID - Syafra, Sitti Nur; Haji, Abdul Gani; Adlim, Adlim; Amsal, Azhar (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
This research was aimed to generate student worksheet based on multiple intelligences (MI) for the sub-chapter of colloid for 11th-grade students. This research used R & D model referred to Borg & Gall. This research follow ten stages of analysis, namely (1) checking of needs; (2) planning; (3) initial development of worksheet's draft; (4) preliminary field testing; (5) main product revision; (6) main field testing; (7) operational product revision; (8) operational field testing; (9) final product revision; (10) implementation and dissemination. The feasibility of student worksheet was reviewed from 5 aspects, content conformity, MI components, linguistic, physical appearance and student worksheet equipment. The average score of quality assessment result by expert validator on product quality was 3.43, with very good category. The percentage of high school chemistry teachers' response in the preliminary field testing, main field testing and operational field testing were 78.89; 83.06 and 86.85 respectively. The student of Inshafuddin High School Banda Aceh responded positively to the student worksheet based on multiple intelligences of the colloid topic with the percentage 88.33. Developed student worksheet based on MI for colloid topics was feasibly applied for learning.